ANALYSIS OF LIQUIDITY RATIOS AND PROFITABILITY RATIOS TO ASSESS FINANCIAL PERFORMANCE - Novi Tri Asiani; Ni Putu Widhia Rahayu (ZILLZELL MEDIA PRIMA, 2024)
PT. GoTo Gojek Tokopedia Tbk experienced a profit that continued to decline from 2019 to 2022. The purpose of this study is to determine how the profitability ratio is seen from gross profit margin, net profit margin, return on assets, and return on equity at PT. GoTo Gojek Tokopedia Tbk for the 2019-2022 period and to find out how the liquidity ratio is seen from the current ratio, quick ratio, and cash ratio at PT. GoTo Gojek Tokopedia Tbk for the 2019-2022 period. The method used is quantitative descriptive analysis by analyzing the company's financial performance data from 2019 to 2022 using financial ratio analysis based on data listed on the Indonesia Stock Exchange and data from the official website of PT. GoTo Gojek Tokopedia Tbk. Based on the results of Liquidity Ratio analysis at PT. GoTo Gojek Tokopedia Tbk can be said to be good. The Profitability Ratio of PT GoTo Tbk is in a poor position, because it tends to decline below the industry average. The company has sufficient ability to guarantee and pay off its debts to creditors. The results of this financial ratio analysis can also be used as an indicator for investors who are interested in investing in PT GoTo Tbk because the company's financial condition remains strong.